Survival of the Print Book! The Falsifiability Approach towards an Inductive Belief - Dariush Alimohammadi (International Journal of Information Science and Management, 2013)
Looks at the historical and philosophical roots of the reasoning and defines the induction as the most popular style of reasoning. Discusses the problem of induction and its complexities through an example. Explains one of the solutions provided for the problem of induction; i.e. the falsifiability theory. Defines the falsifiability theory and concentrates on an ongoing argument among information professionals. Survival of the print book, as an inductive belief, is what this article tries to analyze and gauge. Through an all-inclusive literature review, viewpoints of the pros and cons of this inductive belief are discussed; and much number of evidences is provided for the death of the print book. Concludes that the survival of the print book belief is falsified and liberal information professionals should be trained to press e-book publishers to develop their products.